Digitalization Of The Social Security Sector – A Requirement Of The Time: Reforms In The Social Security System Of Uzbekistan And Their Effectiveness - Mahmudjon Ziyadullayev Jurakulovich (Genius Publishing Group, 2025)
This article examines the reforms being carried out in the Republic of Uzbekistan in the field of social protection, including pension provision, the conveniences created for citizens, and international experience. It also provides detailed information on the experience of developed countries in granting pensions using the “proactive” method, with a particular focus on the Dutch pension system. In the concluding section, along with the implementation of the “proactive” pension assignment method, proposals are put forward to allow citizens to submit additional documents as needed
Keywords: Proactive; pension; social protection